2017
DOI: 10.1002/ange.201707491
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Inspired Carbon Monoxide Sensors with Voltage‐Activated Sensitivity

Abstract: Correspondence to: Timothy M. Swager. + These authors contributed equally to this work.Supporting information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.org/ 10.1002/anie.201707491. Conflict of interestThe authors declare the following competing financial interest(s): A patent has been filed on this technology. HHS Public Access Author Manuscript Author ManuscriptAuthor Manuscript Author ManuscriptCarbon monoxide (CO) outcompetes oxygen when bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…The recent developments show that the more traditionally explored systems combining porphyrins with graphene or carbon nanotubes are still valid sensing systems, especially for the electrochemical detection of metal ions (Cd 2+ , Fe 3+ , Zn 2+ [28,33,38]) or compounds of biological relevance in aqueous media [25,[29][30][31]37]. Furthermore, novel configurations in FET devices using porphyrins/CNMs are increasingly used in chemical [43,44] and biological sensors fabrication, the latter commonly exploiting aptamer sensing strategy [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent developments show that the more traditionally explored systems combining porphyrins with graphene or carbon nanotubes are still valid sensing systems, especially for the electrochemical detection of metal ions (Cd 2+ , Fe 3+ , Zn 2+ [28,33,38]) or compounds of biological relevance in aqueous media [25,[29][30][31]37]. Furthermore, novel configurations in FET devices using porphyrins/CNMs are increasingly used in chemical [43,44] and biological sensors fabrication, the latter commonly exploiting aptamer sensing strategy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the neural model outperformed PLSR obtained satisfactory capacity in accurately predict concentrations. In the case of FET devices, Swager et al found that gate voltage may modulate the sensitivity of sensors based on F-SWCNTs and FeTPPClO 4 , which serves as redox active CO binding site [43]. UV-VIS spectroscopy, differential pulse voltammetry, and density functional theory reveal that the porphyrin is responsible for the in-situ reduction of Fe III to Fe II , which in turn enhances the interaction between the F-SWCNTs and CO. As above mentioned, one of the main novelties of the work is the possibility to modulate (in this case amplifying) the sensitivity to CO when negative gate voltage is applied.…”
Section: Carbon Nanotubes@porphyrin Sensorsmentioning
confidence: 99%
“…[335] With the advancements of technology, developed sensors can accurately and selectively quantify humidity, [336][337][338][339] volatile organic compounds (i.e., ethanol, acetone, methanol, formaldehyde), [313,336,338] and noncondensable gases (i.e., hydrogen, carbon monoxide, carbon dioxide). [340] Humidity sensors have been inspired by weak molecular interactions and bonds [336,337] to the photonic structures of beetle wing-cases. [338,339] Weak noncovalent interactions between proteins and molecules lead to supramolecular assemblies and disassemblies, which can be detected at a cellular level.…”
Section: Gasmentioning
confidence: 99%
“…[313] While most of the mentioned gas sensors are quantified through visual observations (i.e., wrinkling, swelling, and color alteration), there are still those whose molecular interactions are measured through circuit resistance. [336,337,340] It was observed that the sensor sensitivity increased through the application of a negative voltage gate, enhancing the interaction of noncondensable gas (i.e., carbon monoxide) with the fabricated sensor con-taining iron porphyrin and functionalized single-walled carbon nanotubes. [340]…”
Section: Gasmentioning
confidence: 99%
See 1 more Smart Citation